PERAN PENGAWASAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PEMBANGUNAN DI DESA BATU KE’DE KECAMATAN MASALLE KABUPATEN ENREKANG - Safira, Liya; Malik, Ihyani; Hawing, Hardianto (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine the role of BPD supervision in development in Batu Ke'de Village. The village government in this research collected data through interviews, observation and documentation. Data analysis through data reduction, data presentation and inference, the results of the research show that the BPD of Batu Ke'de Village in carrying out its BPD supervisory role has 4 dimensions, namely standards, determination of measurements, which can be seen in the implementation of the supervisory duties of the village treasury BPD in Batu Ke'de Village. determining activity performance measurements, measuring activities and comparing activities with standards, as well as deviation analysis are basically carried out correctly and in accordance with the SOP provided. Barriers to BPD in carrying out supervisory duties are the low level of education of BPD members, conflicts of interest, and inadequate allocation of BPD operational resources.